AB0757 ASSOCIATION BETWEEN DEPRESSIVE SYMPTOMS AND ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH PSORIATIC ARTHRITIS. (13th June 2020) - De Lorenzis, E.; DI Giorgio, A.; Natalello, G.; Nesci, A.; Bruno, D.; Lucchetti, D.; Tanti, G.; DI Mario, C.; Rubortone, P.; Magurano, M. R.; Tolusso, B.; Santoliquido, A.; et al.
Abstract : Background: Cardiovascular complications are the leading cause of death in patients with psoriatic arthritis (PsA), but current strategies for reducing cardiovascular risk are still inadequate. Depression is a common comorbidity in PsA patients and it is recognized as an independent cardiovascular risk factor in the general population. Endothelial dysfunction, assessed as a reduction in brachial artery Flow Mediated Dilation (FMD), is a predictor of major cardiovascular events in high and low risk populations. Objectives: To investigate the relationship between endothelial function and depressive symptoms in a cohort of patients with PsA. Methods: Sixty consecutive patients with PsA, aged between 30 and 79 years, with no history of major cardiovascular events, were characterized for traditional cardiovascular risk factors and features of psoriatic disease. The risk of cardiovascular events according to traditional risk factors was calculated using the Framingham Risk Score (FRS) and the presence of depressive symptoms was defined through the Hospital Anxiety and Depression Scale (HDS) using the validated cut-off of 8. Endothelial function was assessed by FMD. Serum IL-6 was quantified by ELISA, IL-17 and TNF-α levels by Luminex method. Results: Patients had an average age of 52.1±11.0 years, 43.3% of them were male, 23.3% obese and 25.0% active smokers; 38.3%, 25.0% and 11.7% were treated for high blood pressure, dyslipidemia and diabetes mellitus, respectively. The 10-year risk of major cardiovascular events estimated by FRS was 10.4%. The mean duration of PsA was 9.4 years, 30.0% of patients were in minimal disease activity (MDA) and 61.7% and 46.7% were treated with conventional and biotechnological DMARDs, respectively. The mean HDS value was 6.9±3.2 and 43.4% of patients had significant depressive symptoms. The severity of depressive symptoms according to HDS correlated with disease activity according to DAPSA (r=0.449, p=0.001). The mean FMD was 7.8±3.8%, this value correlated inversely with age (r=-0.408, p<0.001), risk of major cardiovascular events according to FRS (r=-0.327, p=0.011) and severity of depressive symptoms according to HDS (r=-0.285, p=0.027). The correlation between FMD and serum IL-6, IL-17 and TNF-alpha levels was not statistically significant. In multivariate linear regression models, the relationship between FMD and HDS was significant also when corrected for age (β=-0.26, p=0.03, R 2 =0.23) and FRS normalized through logarithmic transformation (β=-0.32, p=0.009, R 2 =0.22). Conclusion: The degree of endothelial dysfunction quantified by FRS correlates with the severity of the depressive symptoms in patients with PsA, independently of the cardiovascular risk attributable to classical risk factors. The weak relationship between FRS and serum levels of IL-6, IL-17 and TNF-alpha suggests a role of factors independent of inflammation in the regulation of endothelial function in patients with PsA. Systematic research and treatment of depressive symptoms could contribute to a more complete stratification and a better management of cardiovascular risk in patients with PsA. Disclosure of Interests: Enrico De Lorenzis: None declared, Angela Di Giorgio: None declared, Gerlando Natalello: None declared, Antonio Nesci: None declared, Dario Bruno: None declared, Donatella Lucchetti: None declared, Giacomo Tanti: None declared, Clara Di Mario: None declared, Pietro Rubortone: None declared, Maria Rosaria Magurano: None declared, Barbara Tolusso: None declared, Angelo Santoliquido: None declared, Giusy Peluso: None declared, Elisa Gremese Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer